Portrait of students’ language politeness in elementary school - Ari Susandi; Zamzani Zamzani; Mulyo Prabowo; Bambang Yulianto (International Journal of Evaluation and Research in Education (IJERE), 2024)
This study described students’ language impoliteness during the Indonesian language learning process taking place at elementary school in the Kediri Regency, East Java Province, Indonesia. This study used a qualitative approach to the type of qualitative descriptive research. The research participant of this study were elementary school educators and students in Kediri, East Java, Indonesia, who have a rough and smooth Javanese language culture when communicating with teachers during the learning process in class. The results of the study showed that all politeness maxims were violated in the learning process. Language politeness must continue to be implemented in elementary schools because it is still being discovered violation of the maxim of wisdom is shown when students give long-winded statements to educators. Violation of the maxim of generosity is shown when students give emotional statements to educators. Violation of the maxim of praise is shown when students express criticism at will, to both educators and friends. Violation of the maxim of politeness is shown when students make statements that demean the speech partner. Violation of the maxim of agreement can be seen when students are giving very harsh statements and ignoring the rules of the speech partners. The violation of the maxim of sympathy is shown when students do not have sympathy for the speech partner who is having difficulty. Language politeness is very important for the world of education as an effort to familiarize students as the nation’s next generation with polite language.